Synthesis of the O-linked hexasaccharide containing b-D-Galp-(1→2)- D-Galf in Trypanosoma cruzi mucins. Differences on sialylation by trans-sialidase of the two constituent hexasaccharides - Agusti, Rosalia (2015)
The hexasaccharide b-D-Galp-(1?2)-[b-D-Galp-(1?3)]-b-D-Galp-(1?6)-[b-D-Galp(1?2)-b-D-Galf(1?4)]- D-GlcNAc (10) and its b-D-Galf-(1?2)-b-D-Galf containing isomer (7) are the largest carbohydrates in mucins of some strains of Trypanosoma cruzi. The terminal b-D-Galp units are sites of sialylation by the parasite trans-sialidase. Hexasaccharide 10 was chemically synthesized for the first time by a [3+3] nitrilium based convergent approach, using the trichloroacetimidate method of glycosylation. The 1 H NMR spectrum of its alditol was identical to the spectrum of the product released by b-elimination from the parasite mucin. The trans-sialylation reaction studied on the benzyl glycoside of 10 showed two monosialylated products whose relative abundance changed with time. On the other hand, only one product was produced by sialylation of the benzyl glycoside of 7. A preparative synthesis of the latter and spectroscopic analysis of the product unequivocally established the sialylation site at the less hindered (1?3)-linked galactopyranose.